Crystal structure of dichloridodimethylbis(tri-4-tolylphosphane oxide-κO)-tin(IV), C44H48Cl2O2P2Sn - Lee, See Mun *; Lo, Kong Mun *; Tiekink, Edward R. T. * (De Gruyter Open, 2020)
C44H48Cl2O2P2Sn, orthorhombic, Pbca (no. 61), a = 17.8312(1) Å, b = 12.0291(1) Å, c = 18.5895(1) Å, V = 3987.32(5) Å3, Z = 4, Rgt(F) = 0.0196, wRref(F2) = 0.0564, T = 100(2) K.